Video explanations as a useful digital source of education in the COVID 19 situation - Pestano Pérez, Manuel (Revija za elementarno izobraževanje, 2020)
The paper presents the current state of scientific findings on flipped learning during the outbreak of COVID 19 and compares two models, the Chinese and the Slovenian. The portal www.razlagamo.si offers asynchronous video explanations that allow the learner to manage time independently and supportive conversations in which students synchronously, in one-to-one conversations communicate with studentteachers and in-service teachers. The quantitative overview of the video explanations is provided. Results will help teachers who use the principles of flipped classroom, and decision-makers who design the educational model for the future.
Keywords: asinhrono učenje; asynchronous learning; China; digital resources; digitalni viri; flipped classroom; Kitajska; obrnjena učilnica; Slovenia; Slovenija